2006
DOI: 10.3171/jns.2006.104.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Lack of value of routine analysis of cerebrospinal fluid for prediction and diagnosis of external drainage–related bacterial meningitis

Abstract: Object. Routine microbiological and chemical analysis of cerebrospinal fluid (CSF) is often performed to diagnose external drainage-related bacterial meningitis (ED-BM) at an early stage. A cohort study was performed to investigate the value of several commonly used CSF parameters for the prediction and diagnosis of ED-BM.Methods. In a cohort of 230 consecutive patients in whom external drains had been placed, CSF samples were collected daily, prospectively evaluated for the presence of bacteria using Gram sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
114
2
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 28 publications
1
114
2
8
Order By: Relevance
“…This would give different results from those used in our paper, which we consider to be more relevant to EVD catheter conditions in use. Their study covered only the first 24 hours, but samples of CSF for diagnosis are unlikely to be obtained so early after placement of the catheter, and practice varies: some obtain samples at 3 or 5 days, some 3 times weekly, and some only if clinically indicated, [5][6][7]14 and clinical concern regarding infection usually does not arise so soon as within 24 hours after placement. 8,9,15 The detection method of Stevens et al for drug release (capillary electrophoresis) did not allow quantitative determination of actual drug levels in the saline, whereas our methods (HPLC and LC-MS) were able to accurately determine the concentrations of drugs in the perfusates at each time point.…”
Section: Discussionmentioning
confidence: 99%
“…This would give different results from those used in our paper, which we consider to be more relevant to EVD catheter conditions in use. Their study covered only the first 24 hours, but samples of CSF for diagnosis are unlikely to be obtained so early after placement of the catheter, and practice varies: some obtain samples at 3 or 5 days, some 3 times weekly, and some only if clinically indicated, [5][6][7]14 and clinical concern regarding infection usually does not arise so soon as within 24 hours after placement. 8,9,15 The detection method of Stevens et al for drug release (capillary electrophoresis) did not allow quantitative determination of actual drug levels in the saline, whereas our methods (HPLC and LC-MS) were able to accurately determine the concentrations of drugs in the perfusates at each time point.…”
Section: Discussionmentioning
confidence: 99%
“…Note that CSF may not need to be obtained if another clear source of infection has been identified. Changes in CSF parameters may be subtle [14], thus making it hard to determine if the abnormalities are related to infection or secondary to the underlying reason for catheter placement or a result of neurosurgery [55,56]. Although high CSF white blood cell counts correlate with the presence of infection, infection may be present even in patients with normal CSF white blood cell counts.…”
Section: Evidence Summarymentioning
confidence: 99%
“…All 7 patients with infection had fever (>38.5°C) and peripheral leukocytosis (>11 000/mm 3 ) on the day the infection was identified, and 1 had a change in CSF appearance. A prospective study also demonstrated no value of routine analysis of CSF for prediction and diagnosis of external drain-related bacterial meningitis [56]. Another study assessed whether the incidence of ventriculitis changed when CSF sampling frequency was reduced to once every 3 days [152].…”
Section: Evidence Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that elevated temperatures and abnormal blood and CSF studies are poor predictors of CNS infections after large cranial procedures, especially in children. 12,14 It should be recognized that our clinicolaboratory associations could be related to other variables strongly linked with etiology, such as perioperative blood loss and intravenous fluid management, as previously reported. 3 Why some seizure etiologies are associated with differential changes in blood and CSF studies rather than other etiologies is unclear and not a component of the present study design.…”
Section: Discussionmentioning
confidence: 94%